Indikator Perilaku Konsumen Dalam Memenuhi Kebutuhan Primer (Studi Maslahah Imam Al-Gazali Kitab Al Mustasfa Min ‘Ilm Ushul) - Miftahul Huda (University of Darussalam Gontor, 2017)
Consumer behavior is a human attitude in utilizing its income in meeting the needs, both individually and socially. The problem of human economy in the perspective of Islam is the fulfillment of need with Natural Resources (SDA), with the concept of maslahah is expected to assist in fulfilling the welfare of human life present. Imam Al-Ghazali has previously introduced the concept of social welfare function, in which we are required to distinguish the needs of dharuriyyat, hajiyyat, and tahsiniyyat is a matter which must Observed, lest we be wrong in determining the category level tesebut. Introduction in meeting the needs of priority scale has been introduced since the first although not yet reviewed in detail. The application al-ushul al-khamsah in meeting human needs has been facilitated by its development to date. The universal value that belongs to its own value in guarding the behavior of a consumer to become an Islamic Man.